Rosmarinic Acid – Pharmaceutical and Clinical Aspects - Amoah, Solomon K. S.; Sandjo, Louis P.; Kratz, Jadel M.; Biavatti, Maique W. (Planta Medica, 2016)
The biosynthesis and biotechnological production of Rosmarinic acid, a phenolic ester that is widespread in the plant kingdom, has been widely investigated. This compound has shown many remarkable biological and pharmacological activities, which have led to its pharmaceutical and analytical development, as well as clinical studies, which are summarized and analyzed here for the first time. This review compiles data from the Pubmed, Scopus, Scifinder, Web Of Science, and Science Direct databases published between 1990 and 2015, restricting the search to works with the keywords “Rosmarinic acid” in the title. The initial search identified more than 800 articles; after an initial screening and removal of duplicate works, the search was further refined, resulting in approximately 300 articles that were scrutinized and comprise this review. The articles were organized to describe extraction and isolation, analytical methods, pharmaceutical development, and biological and pharmacological activities [divided into nonclinical (in vitro, in vivo) and clinical studies], pharmacokinetic studies, and stability studies.
Keywords: rosmarinic acid; isolation and analysis; clinical studies; pharmacokinetics; pharmaceutical development